From Ground to Sky: Legal Review of Flat Development in Cirebon under Apartment Law - Rinaldi, Farrel Ardan (Indonesian Journal of Agrarian Law, 2024)
Technological developments and rapid population growth are driving the need for adequate housing, especially in increasingly dense urban areas. In efforts to realize a just and prosperous society, the construction of flats is a strategic solution that can address the challenges of limited land and the increasing demand for housing in urban areas. Demographic projections indicate that by 2030, approximately 70% of Indonesia's population will live in urban areas, making the provision of flats an unavoidable urgency. Cirebon City, as a strategic city located on the main connecting route to Java Island, is experiencing rapid development in various sectors, including infrastructure and spatial planning. With a population of 343,497 and a density of 9,194 people/km² in 2021, pressure on space is increasing, demanding efficient vertical housing planning. The construction and expansion of flats in Cirebon City not only plays a role in meeting housing needs but also supports the existence of public spaces, social interaction, and ecological balance. Therefore, spatial management strategies and the development of vertical housing are crucial aspects in responding to the dynamics of urbanization in Cirebon City.